Penggunaan Tema Visual Dalam Feed Instagram Untuk Meningkatkan Keterlibatan Pengikut : Studi Kasus Pada Akun Instagram @Gteamagency - Luthfi, Atsilia Rofi'atul; Riyanto, Buddy; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
One of the effective and interesting forms of communication is Visual Communication Design. Visual Communication Design is a discipline that is closely related to the concept of communication. This research aims to describe how the use of visual themes in Instagram feeds can increase follower engagement. This case study was conducted on the Instagram account of gteam.agency, a social media agency that uses a consistent and attractive visual theme. This research uses descriptive qualitative research. Data collection methods used interviews, observation, and documentation. The data were analyzed using the Uses & Gratification theory. The results show that the use of good and consistent visual themes plays an important role in increasing engagement and success on social media platforms such as Instagram. An attractive visual theme can attract followers' attention, increase brand awareness, and encourage interaction.